Functionalized mesoporous silica for the control of crystallization fouling - Lapidot,T; Heng,JYY (Industrial & Engineering Chemistry Research, 2016)
A seeding study to test the effectiveness of nanoparticles in mitigating crystallization fouling is reported. The effect of functionalized mesoporous silica particles on calcium sulfate crystallization was studied through a series of batch crystallization experiments. Tested surface chemistries include nonfunctionalized silica (hydrophilic), methyl (hydrophobic) propyl amine (basic), propyl sulfonic acid (acidic), and triaminetetraacitic acid (TAAcOH, chelating). Crystallization was tracked online using electrical conductivity to determine concentration as a function of time, which was used to calculate induction time and growth rate. At a loading of 0.1 mg/gsol, amine functionalized particles were found to be the most effective at reducing induction time, while TAAcOH particles were found to significantly increase induction time. The efficacy of TAAcOH particles was further tested at various loadings and was found to increase induction time 6-fold at a loading of 0.5 mg/gsol. Despite having a profound effect on induction time, growth rates remained relatively constant for all surface chemistries and loadings. Here, we show that the seed surface chemistry can play a major role in the control of calcium sulfate crystallization.